Architectural and artistic features of the entrance portal of the church in Velykyi Khodachkiv of Ternopil region - N. Yavna (Architectural Studies, 2022)
The design of the main entrances in cathedrals and churches has always been one of the main tasks of artists. Realising the importance of the entrance to the Temple of God, the sculptors tried to design it in the form of a portal and give it prominence with an original sculpturesque design. This study covers the features of the architectural and artistic structure of the main portal of the Church of the Mother of God in Velykyi Khodachkiv, justifies its artistic value, examines the technical condition of the newly discovered monument, and identifies aspects of the restoration of the portal. Based on the general scientific and special restoration research methods used, the paper investigated the style characteristics of the portal, identified the main reasons for the degradation of the monument, and developed a set of restoration measures. In the study, based on literary sources and field surveys, an attempt to investigate the influence of one of the main architectural elements of the temple decoration – the portal, on the architectonics of the main facade of the shrine was made. Special attention was drawn to the unexplored Velykyi Khodachkiv Church in the Ternopil region, which is in a dilapidated state with an interesting architectural design of the main entrance. The architectural, artistic, and compositional design of the entrance portal of the Church of the Mother of God the Comforter and St. Joseph in Velykyi Khodachkiv was analysed in detail. Its stylistic and proportional solutions were examined. The portal is characterised by the expressiveness of architectural details, the integrity and aesthetics of this work of art were created according to the laws of beauty. Based on a thorough study of the features inherent in the portal, its architectural and artistic value was determined, and its technical condition was investigated. The Church of the Mother of God the Comforter in the former town of Velykyi Khodachkiv, Ternopil region, is not included in the Register of architectural monuments of Ukraine, so there is little information about the monument under study. Overlooked by researchers and art historians, the church has been in ruins for centuries and continues to collapse. The results of the study can be used in the system of historical and architectural education and practical restoration activities